Quinta da Aurora: Arquitectura e Enoturismo - Bernardo Valinhas dos Santos Castelo Ribeiro (2020)
This dissertation is part of an intimate connection with Quinta da Aurora. This place, which has belonged to the family since its construction and which already accounts for the passage of several generations, was the ideal pretext to finish my school path, by intervening in a place that is very close to me and which has proved to be a challenge. Due to the characteristics, both existing and proposed for the property, it was possible to develop topics for which I have a special interest while the focus of the intervention was directed as much as possible to the experience of the spaces in relation to each other and not to their value as an independent element. During the development of the project, some writings were developed that reflect on the issues that showed to be decisive in reaching the final proposal. These texts are not limited to the chapter in which they are presented considering that the actions referred to in them extend to other themes in an attempt to maintain a global and cohesive language throughout exercise.